2019
DOI: 10.1123/ijspp.2018-0349
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Force–Time Characteristics After Australian Rules Football Matches: Examining the Utility of the Isometric Midthigh Pull

Abstract: Purpose: This study assessed the utility of force–time characteristics from the isometric midthigh pull (IMTP) as a measure of neuromuscular function after elite-level Australian rules football matches. It was hypothesized that rate characteristics of force development would demonstrate a different response magnitude and recovery time course than peak force measurements. Methods: Force–time characteristics of the IMTP (peak force, 0- to 50-ms rate of force development [RFD], 100- to 200-ms RFD) were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…The RPD during the CMJs concentric phase was considered reliable in the current study and is in agreement with the limited prior findings (ICC = 0.89-0.99; CV = 4.6-9.9%) [19,32,33,47]. Although RFD is often regarded as a key performance indicator for athletic performances [25][26][27], multiple studies have now called into question its inherent reliability. This makes RFD less than adequate for monitoring neuromuscular readiness and fatigue, as large changes will be necessary to overcome the standard error in the measurement (i.e., the changes observed in RFD may or may not be indicative of changes in neuromuscular status).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The RPD during the CMJs concentric phase was considered reliable in the current study and is in agreement with the limited prior findings (ICC = 0.89-0.99; CV = 4.6-9.9%) [19,32,33,47]. Although RFD is often regarded as a key performance indicator for athletic performances [25][26][27], multiple studies have now called into question its inherent reliability. This makes RFD less than adequate for monitoring neuromuscular readiness and fatigue, as large changes will be necessary to overcome the standard error in the measurement (i.e., the changes observed in RFD may or may not be indicative of changes in neuromuscular status).…”
Section: Discussionsupporting
confidence: 90%
“…The volume of metrics provided by such companies is also concerning, as some variables may be more reliable during testing and, thus, more sensitive to change in the neuromuscular status of an individual [23,24]. For example, RFD is a popular variable derived from force plate testing that previous studies have identified as an acceptable strategy for monitoring athlete performance [25,26], as well as neuromuscular fatigue [26,27]. However, other studies demonstrated that RFD was unreliable and, thus, should be used in athlete monitoring with excess caution [6,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged perturbations (based on ES values) seen in some (i.e., F250), but not other (i.e., PF) variables suggest that maximal force production may be less sensitive to the influence of match-play when compared to those measures that include a velocity-component. This finding supports observations following Australian Rules Football match-play, in which the rate of force development was found to be more sensitive to the recovery of neuromuscular function than PF [44]. When performing sporting actions such as sprinting, jumping and changing direction, ground contact occurs in time intervals between 50-250 ms, therefore it may be more important to apply force quickly as opposed to producing maximal force [45].…”
Section: Discussionsupporting
confidence: 86%
“…Whilst responses to rugby match-play have been profiled using different measures, such as a CMJ [4,7,11], a plyometric push-up [14], and an adductor squeeze test [16], the present study is amongst the first to profile the effects of match-play on IMTP responses [44]. Although match-play did not influence PF during the IMTP, a large ES (0.95) was reported at +24 h following match-play compared to baseline measures, whilst small and trivial ES were observed thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Strong correlations (r ≥ 0.70) have been observed between these variables and weightlifting performance [12,13,14]. However, research suggests that RFD is more closely related to most athletic tasks [15,16] and is more sensitive to fatigue [12,17]. Haff et al [18] reported that calculating RFD using specific time bands results in higher reliability than quantifying peak RFD values.…”
Section: Introductionmentioning
confidence: 99%